STRUKTUR DIALOGIS AL-QUR’AN DALAM KAIDAH AS-SU’ĀL WA AL-JAWĀB: ANALISIS RETORIKA DAN IMPLIKASI HERMENEUTIS - Sukmawati, Sukmawati; Miswar, Andi; Ilyas, Hamka (EL-MAQRA', 2026)
This study examines the dialogical structure of the Qur’an in the principle of as-su’āl wa al-jawāb through rhetorical analysis and its hermeneutical implications in Qur’anic interpretation. The research employs a qualitative method with a library research approach by integrating thematic exegesis, Qur’anic rhetoric, and pragmatic linguistics. Primary data consist of Qur’anic verses containing patterns of questions and answers, while secondary data are derived from classical and contemporary tafsir literature and related scholarly works. The findings reveal that the pattern of as-su’āl wa al-jawāb functions not merely as a linguistic communication device, but also as a rhetorical strategy with persuasive, educational, argumentative, and spiritual dimensions. The dialogical structure of the Qur’an further demonstrates non-linear response patterns that influence the interpretive process of Qur’anic verses. This study contributes to the development of contemporary Qur’anic interpretation by integrating rhetorical, hermeneutical, and pragmatic approaches in understanding the dialogical communication of revelation.